FEATURES OF THE CLINICAL COURSE OF CHICKENPOX IN ADULTS IN THE KHOREZM REGION (UZBEKISTAN) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Chickenpox is generally considered a childhood infection. However, cases of the disease in adults, although less common, are characterized by a more severe clinical course and a high risk of complications. This article presents the results of a retrospective analysis of clinical data from 23 adult patients (aged 23-40 years) hospitalized with chickenpox in the Khorezm region (Uzbekistan). The study assessed the clinical features, the presence of complications, and factors contributing to a more severe course of the disease. The results showed that the majority of patients had severe intoxication, profuse rash, high fever and a longer period of rashes compared with the classic course of chickenpox in children. The most common complications were pneumonia and secondary bacterial infection of the skin. Potential risk factors for severe course have been identified, including the presence of concomitant chronic diseases and late medical treatment. The findings highlight the importance of timely diagnosis and adequate treatment of chickenpox in adults, as well as the need to develop regional infection prevention and control strategies.